Pengaruh Gaya Kepemimpinan, Motivasi Kerja dan Budaya Organisasi terhadap Kinerja Karyawan Pada Kantor Desa Tibubeneng - Purnamawati, Ni Putu Indah; Putu Kawiana, I Gede; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Human resources (HR) are the most valuable assets owned by agencies, organizations or companies. Because its existence is very related to the dynamics of company mobilization. Therefore, many companies are always trying to improve the quality of their resources so they can carry out their work activities to the fullest. The purpose of this research is to determine the effect of leadership style, work motivation, and organizational culture on employee performance. The data used is quantitative primary data which will be obtained from distributing questionnaires. The number of samples used in this study were 33 respondents. The data collection technique used is in the form of a questionnaire. The analysis technique uses multiple linear regression. The results of this study indicate that leadership style, work motivation, and organizational culture simultaneously have a positive and significant influence on employee performance. Leadership style partially has a positive and significant effect on employee performance, where if the leadership style increases, employee performance increases. Work motivation partially has a positive and significant effect on employee performance, where if work motivation increases, employee performance increases. Organizational culture partially has a positive and significant effect on employee performance, where if organizational culture increases, employee performance increases